Technology Readiness and Nurses' Acceptance Model Towards the Implementation of Electronic Medical Record (EMR) at Hospital X Tangerang - Saputra, Muhammad Rian; Rahmad, Tantri Yanuar; Dewi, Sandra (Alta Dharma Publisher, 2025)
Introduction: One of the hospital's efforts to improve the quality of medical care is by implementing an electronic medical record (EMR). This depends on individual readiness factors and the acceptance of new technologies in hospital EMR implementation. Objective: The study aims to analyze the readiness of technology and nurse acceptance models for the implementation of EMR. Method: This study uses a quantitative approach with exploratory objectives. This study used a questionnaire to sample 264 respondents (nurses), as well as SEM (structural equation modeling) as a data analyst. The study results showed that of the 11 existing hypotheses, two hypotheses were rejected: insecurity against perceived ease of use with a p-value of 0.761 > p-value 0.05 and discomfort against perceived usefulness with a p-value of 0.156 > p-value 0.05. Results: The results of the study show that the futility of individuals and models of accepting new technology through factors such as optimism, innovativeness, insecurity discomfort, as well as perceived ease of use and perceived usefulness can influence Indovidu in accepting new technologies, such as electronic medical records Recommendation of your study must be clear. The abstract also should not contain any references or display an equation